Concurrent task performance enhances low-level visuomotor learning. - O'MARA, SHANE MICHAEL; ROCHE, RICHARD (Psychonomic Society, 2007)
Visuomotor association learning involves learning to make a motor response to an arbitrary visual stimulus. This learning is essential for visual search and discrimination performance and is reliant upon a well-defined neural circuit in the brain that includes the prefrontal cortex and the hippocampal formation. In the present study, we investigated the possible role of attentional processes during such learning using dual-task interference. A motor, verbal, or perceptual concurrent task was performed during the learning/training block of a simple visual discrimination task. Contrary to expectation, the dual-task groups showed improved learning and learning-dependent performance compared with untrained control and non-dual-task trained groups. A second experiment revealed that this effect did not appear to be due to increased arousal level; the inclusion of alerting tones during learning did not result in facilitation. These findings suggest that the engagement of attention, but not arousal, during the acquisition of a visuomotor association can facilitate this learning and its expression.
PUBLISHED
Keywords: Administrative Staff Authors